Farnesoid X Receptor Agonists as Therapeutic Target for Cardiometabolic Diseases - Li, Chao; Yang, Jie; Wang, Yu; Qi, Yingzi; Yang, Wenqing; Li, Yunlun (Frontiers in Pharmacology, 2020)
Cardiometabolic diseases are characterized as a combination of multiple risk factors for cardiovascular disease (CVD) and metabolic diseases including diabetes mellitus and dyslipidemia. Cardiometabolic diseases are closely associated with cell glucose and lipid metabolism, inflammatory response and mitochondrial function. Farnesoid X Receptor (FXR), a metabolic nuclear receptor, are found to be activated by primary BAs such as chenodeoxycholic acid (CDCA), cholic acid (CA) and synthetic agonists such as obeticholic acid (OCA). FXR plays crucial roles in regulating cholesterol homeostasis, lipid metabolism, glucose metabolism, and intestinal microorganism. Recently, emerging evidence suggests that FXR agonists are functional for metabolic syndrome and cardiovascular diseases and are considered as a potential therapeutic agent. This review will discuss the pathological mechanism of cardiometabolic disease and reviews the potential mechanisms of FXR agonists in the treatment of cardiometabolic disease.